Roll-to-roll manufacture of flexible thin-film thermoelectric generators using flexography with vacuum vapour deposition - Tao, X; Stuart, BW; Assender, HE (Elsevier, 2022)
Exploring processes for industrial large-scale manufacture of low-cost electronics devices is timely for the upcoming era of the Internet of Things. In this study, a roll-to-roll process using selective metallisation (a combination of flexographic printing of an oil liquid-mask and physical vapour deposition: sputtering and evaporation) is explored for the large-scale manufacture of flexible electronics, with a wearable thermoelectric generator as an exemplar device. Two post-treatments (electron beam and infrared) are trialled to remove the residual oil after selective metallisation. Both are effective for the removal of oil, however, the oil used in selective metallisation degrades the functional thermoelectric material severely, causing a dramatic increase in the internal resistance of the device. This is attributable to (1) the doping and oxidation issues in the semiconductor film; (2) the existence of oil at the interface between the two coatings. The fabricated thermoelectric generator with post-treatments shows a good voltage output comparable to a standard device fabricated using shadow mask, providing an option for portable devices requiring a voltage source. This study reports an industrially compatible roll-to-roll manufacturing process for large-scale manufacture of flexible electronics. Further studies are under way to optimise the device performance.